ASSESSMENT OF NEUROLOGICAL COMPLICATIONS IN CHILDREN PRESENTING WITH PLASMODIUM VIVAX MALARIA - Karim, Rahida; Jahanzeb Khan Afridi; Shabnum Masood; Muhammad Batoor Zaman; Sobia Naeem; Maha Amjad (Journal of Postgraduate Medical Institute, 2023)
Objective: To assess neurological complications in children presenting with Plasmodium vivax malaria at a Tertiary Care Hospital of Peshawar. Methodology: This descriptive cross sectional study was carried out in the Pediatric Department, Hayatabad Medical Complex, Peshawar from April 2021 to September 2021. A total of 183 patients were enrolled using convenient sampling from outpatient department with high grade fever, nausea, diarrhea, and headache, duly confirmed for Plasmodium vivax mono-infection microscopically. A pre-designed performa was used to extract information regarding demographics, laboratory investigations, and neurological complications. SPSS (version 21.0) was used to check the statistics. Results: Out of 183 cases 71.6% were male. The mean age of the patients was 6.44±2.46 years, while mean weight was 12.76±4.56 kg. In mean duration of disease, it was recorded to be as 6.14±2.18 days. The laboratory investigations showed, low level of hemoglobin and platelets count in 38.8% and 42.2% respectively. Neurological complications were detected in 15.8% of children and were non significantly associated with gender, age group and duration of disease (stratified), and was significantly associated with the stratification of hemoglobin, hematocrit levels and platelets count. Conclusion: A less frequent number children reported to have neurological complications when diagnosed with P. vivax. Furthermore, these complications are associated significantly with the stratification of hemoglobin, hematocrit levels and platelets count.